Class A1 scavenger receptor modulates glioma progression by regulating M2-like tumor-associated macrophage polarization - Zhang, Hanwen (Oncotarget, 2016)
Macrophages enhance glioma development and progression by shaping the tumor microenvironment. Class A1 scavenger receptor (SR-A1), a pattern recognition receptor primarily expressed in macrophages, is up-regulated in many human solid tumors. We found that SR-A1 expression in 136 human gliomas was positively correlated with tumor grade (P<0.01), but not prognosis or tumor recurrence. SR-A1-expressing macrophages originated primarily from circulating monocytes attracted to tumor tissue, and were almost twice as numerous as resident microglia in glioma tissues (P<0.001). The effects of SR-A1 on glioma proliferation and invasion were assessed in vivo using an SR-A1-deficient murine orthotopic glioma model. SR-A1 deletion promoted M2-like tumor-associated macrophage (TAM) polarization in mice by activating STAT3 and STAT6, which resulted in robust orthotopic glioma proliferation and angiogenesis. Finally, we found that HSP70 might be an endogenous ligand that activates SR-A1-dependent anti-tumorigenic pathways in gliomas, although its expression does not appear informative for diagnostic purposes. Our findings demonstrate a relationship between TAMs, SR-A1 expression and glioma growth and provide new insights into the pathogenic role of TAMs in glioma.